Dampak Algoritma Media Sosial Terhadap Narasi Keislaman: Tantangan Dan Strategi Literasi Digital (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
The high penetration of the internet in Indonesia has changed the pattern of religious information consumption among the public, particularly through social media controlled by algorithms. These algorithms play a role in determining the Islamic content that appears on users timelines, often prioritising popular and sensational narratives over in-depth and moderate analyses. This study aims to analyse how social media algorithms shape Islamic narratives and explore the role of digital literacy in enhancing users critical awareness. The method used is qualitative-descriptive, with data collection techniques including literature review and digital observation. The results of the study indicate that algorithms create filter bubbles and echo chambers, increasing the risk of religious polarisation. Digital literacy is necessary for users to critically filter information and select credible sources.